Embargo as an Act of International Law Enforcement - Charlos Josse Silooy; Josina Augustina Yvonne Wattimena; Welly Angela Riry (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2025)
,,This research was motivated by the invasion carried out by Russia against Ukraine, which caused other countries such as the United States and its allies to take a stance by imposing an embargo on Russia. The purpose of this study is to determine whether an embargo can be implemented as a law enforcement measure and its impact on countries that violate international law. The research method used in this study is normative legal research, namely by analyzing legal problems in laws and regulations that are related to the problem being studied. The problem approach used is a conceptual approach, using primary legal material sources as a reference to complete the writing and collection of legal materials carried out using library techniques. Based on the research results, an embargo can be carried out as an international law enforcement measure by the Security Council as regulated in Article 41 of the UN Charter as an action that does not use armed force (non-military) in maintaining world security and peace. An embargo is an international law enforcement measure that is soft in the sense that this action is gentle and not harsh like the use of aggressive military. The impact of an embargo on a country that violates international law against another country such as Russia does not have a significant impact. However, the impact of implementing an embargo is that the embargo can put pressure on countries that violate international law to return to complying with international law. The implementation of an embargo must be carried out carefully so that it does not have a broad impact on human rights such as women, children and the elderly.